William Howard Taft papers - Taft, William Howard, 1915 August 7-
Chiefly correspondence between Taft and his parents, Robert A. and Martha Wheaton Bowers Taft, especially during his years as a student at the Taft School, Yale University, and Princeton University. Also includes a letter of congratulation (1915) from former president William H. Taft to Robert A. Taft on the birth of his son and three letters from Horace Dutton Taft.
Diplomat and public official. Died 1991.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Taft, Horace Dutton, -- 1861-1943 -- Correspondence; Taft, Robert A. -- 1889-1953 -- Correspondence; Taft, Martha Wheaton Bowers, -- 1891-1958 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Princeton University -- Students; Taft School -- Students; Yale University -- Students; Diplomats; Public officials